Conoscenza e divulgazione del patrimonio culturale. Analisi e rilievo del Mausoleo di Sant’Urbano sulla via Appia Antica - Maria Grazia Cianci; Sara Colaceci (Archeomatica, 2022)
The paper focuses on the basilica in Contrada S. Salvatore and the epigean. The Mausoleum of Sant’Urbano is located on the IV mile of the Via Appia Antica. The Italian State acquired the mausoleum in 2021, which became part of the Appia Antica Archaeological Park. This opportunity made it possible to enter into a scientific collaboration agreement between the park, the Department of Architecture of the University of Roma Tre and the Department of Humanities, Philosophy and History of Art of the University of Rome Tor Vergata. The objectives aim at the implementation of study, survey and analysis activities of the artifact.